Cost-effectiveness of sotagliflozin for the treatment of patients with diabetes and recent worsening heart failure - Jaehong Kim; Shanshan Wang; Slaven Sikirica; Jason Shafrin (Becaris Publishing Limited, 2024)
Aim: To assesses the cost-effectiveness of sotagliflozin for the treatment of patients hospitalized with heart failure and comorbid diabetes. Materials & methods: A de novo cost-effectiveness model with a Markov structure was created for patients hospitalized for heart failure with comorbid diabetes. Outcomes of interest included hospital readmissions, emergency department visits and all-cause mortality measured over a 30-year time horizon. Baseline event frequencies were derived from published real-world data studies; sotagliflozin's efficacy was estimated from SOLOIST-WHF. Health benefits were calculated quality-adjusted life years (QALYs). Costs included pharmaceutical costs, rehospitalization, emergency room visits and adverse events. Economic value was measured using the incremental cost-effectiveness ratio (ICER). Results: Sotagliflozin use decreased annualized rehospitalization rates by 34.5% (0.228 vs 0.348, difference: -0.120), annualized emergency department visits by 40.0% (0.091 vs 0.153, difference: -0.061) and annualized mortality by 18.0% (0.298 vs 0.363, difference: -0.065) relative to standard of care, resulting in a net gain in QAYs of 0.425 for sotagliflozin versus standard of care. Incremental costs using sotagliflozin increased by $19,374 over a 30-year time horizon of the patient, driven largely by increased pharmaceutical cost. Estimated ICER for sotagliflozin relative to standard of care was $45,596 per QALY. Conclusion: Sotagliflozin is a cost-effective addition to standard of care for patients hospitalized with heart failure and comorbid diabetes.